Balancing social attitudes and ecological conservation in Taiwan’s wind power development under climate change - Chen, Han-Shen (Frontiers in Environmental Science, 2026)
With the global threat posed by climate change, over 130 countries are aiming for “net-zero emissions by 2050.” This study assessed the attributes of wind power development in Taiwan using a discrete choice experiment and an immersive virtual environment. We assessed the public’s willingness to support ecological compensation and obtained 850 valid responses from 1,012 distributed questionnaires (valid completion percentage: 84.0%). Our analysis revealed two critical findings. First, the respondents emphasized that the spacing between turbines significantly influences their visual impact, highlighting the need to enhance the ecological compensation mechanisms for wind power development and ecosystem preservation. Second, they preferred green energy companies to incorporate conservation trust funds into site planning rather than incur additional consumer costs, underscoring the industry’s growing role in environmental stewardship and shifting societal expectations. Our results contribute to sustainable wind energy development and ecological conservation in Taiwan and align with global efforts to develop environmentally responsible energy solutions.